Comparative study on the economic efficiency of rice culture in a conventional and organic system - Daniela-Elena Şurcă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Economic efficiency is defined by the obtaining of useful economic effects, provided that material, human and financial resources are used rationally. Thus, in general terms, economic efficiency can be defined as the connection between the useful effects obtained from a certain economic activity and the efforts made in the respective activity represented by the expenses related to the production process. The main objective of the study is to highlight the economic efficiency of two system conventional and organic for rice crops. In the context of the achievement of the main objective of the paper, it will be analyze the technical and economic indicators referring to: the dynamics of the surfaces, the average outputs, the budget of revenues and expenditures. The revenue and expenditure budget will highlight certain economic issues, such as the value of production, the costs incurred with this crop, the resulting income and the rate of return. In conclusion, this paper seeks to highlight the best agricultural system in terms of economic efficiency, for rice crops, using the comparative method on the set of indicators analyzed.
Keywords: Q12; Q57; 330; economic efficiency; organic / conventional rice; profit